Rate and predictors of response to glucocorticoid therapy in patients of takayasu arteritis at a tertiary level hospital of Bangladesh: A longitudinal study - Farzana Shumy; Ahmad Mursel Anam; Minhaj Rahim Choudhury; Md Abu Shahin; Syed Atiqul Haq; Md Zahid Amin; Sumayia Minhaj (Indian Journal of Rheumatology)
Objectives: This study aimed to assess the rate of inactive disease in Bangladeshi patients with Takayasu arteritis (TA) treated with prednisolone and to identify the characteristics in patients that may guide in choosing induction therapy. Methods: The longitudinal study enrolled active TA patients who received 1 mg/kg/day of prednisolone. Disease activity was assessed by Indian Takayasu Activity Score - C-Reactive Protein (ITAS-CRP) and ITAS2010 at baseline and after 1, 3, and 6 months. The patients who did not achieve inactive disease or again became active during tapering of prednisolone received methotrexate. Results: Among 12 active TA patients, one patient succumbed to death after 15 days. ITAS2010 1 month after steroid showed a significant difference between remission and nonremission patients (P 0.0001). However, five out of 11 (45.45%) patients became inactive. These five patients had onset of symptoms <15 months prior to the initiation of therapy and had no history of syncope, stroke, and complications such as aortic regurgitation and hypertension. Reappearance of a pulse was noted in three out of 11 patients. The presence of carotidynia (P = 0.03) was a significant predictor for the reappearance of pulse. After 6 months, one patient (9.1%) remained inactive with prednisolone alone and other subjects received methotrexate. Conclusion: The response to prednisolone is variable in TA. The presence of carotidynia was a predictor for the reappearance of pulse. Monotherapy with prednisolone is not a good choice as an induction therapy.